2021
DOI: 10.1080/13683500.2021.1960284
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on different business models of European airlines

Abstract: In addition to social damage, the first wave of the COVID-19 pandemic also caused huge economic losses in the beginning of 2020, especially for companies in the tourism sector. The airline market was no exception. This study examines the significance of the business model of European listed airlineslow cost carriers (LCCs), full service carriers (FSCs)for stock market performance. We use event study on the 11 airlines included in the sample. In terms of cumulative average abnormal returns, i.e. the most signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…Because of the damage done to businesses during COVID-19, existing business models have been impacted (Kökény et al, 2022). Many businesses are rethinking and adjusting their business models to include a sustainable component (Di Vaio et al, 2020).…”
Section: Four-box Business Modelmentioning
confidence: 99%
“…Because of the damage done to businesses during COVID-19, existing business models have been impacted (Kökény et al, 2022). Many businesses are rethinking and adjusting their business models to include a sustainable component (Di Vaio et al, 2020).…”
Section: Four-box Business Modelmentioning
confidence: 99%
“…The results found that the performance of Southwest Airlines, a typical low-cost airline, was much better than full-service airlines. Kökény et al (2021) examine the impact of COVID-19 on the stock market performance of listed European airlines. In addition, the existing studies indicate that the impact of an external shock varies across different airline companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Az ázsiai országokba történő utazásokat már március elején sem ajánlották a turistáknak, majd március 19-én Európában a teljes légiforgalmat felfüggesztették a turisták számára (NEUBURGER-EGGER 2021). Az európai tőzsdéken korábban, már február 24-én, látható volt a hatalmas értékvesztés a légitársaságok pénzügyi eredményeiben (KÖKÉNY et al 2022). Így összességében már februárban látható jelei voltak a turizmus gazdasági visszaesésének, majd márciusban teljesen le is állt a szektor Európában.…”
Section: A Covid19-járvány Jellemzőiunclassified